Understanding Vietnamese chicken farmers’ knowledge and practices related to antimicrobial resistance using an item response theory approach - Nohrborg, Sandra; Nguyen-Thi, Thinh; Xuan, Huyen Nguyen; Lindahl, Johanna; Boqvist, Sofia; Järhult, Josef D.; Magnusson, Ulf (Frontiers in Veterinary Science, 2024)
Antimicrobial resistance (AMR) poses a threat to animal and human health, as well as food security and nutrition. Development of AMR is accelerated by over-and misuse of antimicrobials as seen in many livestock systems, including poultry production. In Vietnam, high AMR levels have been reported previously within poultry production, a sector which is dominated by small-scale farming, even though it is intensifying. This study focuses on understanding small-and medium-scale chicken farmers' knowledge and practices related to AMR by applying an item response theory (IRT) approach, which has several advantages over simpler statistical methods. Farmers representing 305 farms in Thai Nguyen province were interviewed from November 2021 to January 2022, using a structured questionnaire. Results generated with IRT were used in regression models to find associations between farm characteristics, and knowledge and practice levels. Descriptive results showed that almost all farmers could buy veterinary drugs without prescription in the local community, that only one third of the farmers received veterinary professional advice or services, and that the majority of farmers gave antibiotics as a disease preventive measure. Regression analysis showed that multiple farm characteristics were significantly associated to farmers' knowledge and practice scores. In conclusion, the study highlights the complexity when tailoring interventions to move towards more medically rational antibiotic use at farms in a setting with high access to overthe-counter veterinary drugs and low access to veterinary services, since many on-farm factors relevant for the specific context need to be considered.The total poultry population of the country was around 545 million in 130 2022 and poultry production has been increasing since 2016 [36]. ¶